Can Pressure Ulcer be Unpreventable among Terminally ill Cancer Patients? - Nigim, Hasan Ahmed Abu; Salim, Nezar Ahmed (Archives of Clinical and Biomedical Research, 2017)
Background: Pressure ulcers are most common problem encountered the patients, those requiring long-term institutional care. The most important factor to prevent pressure ulcer is pressure redistribution. Ulcers can relieve by two ways: proper patient positioning, and appropriate use of pressure-reducing devices. Pressure ulcers can be related to diabetes, venous insufficiency, or arterial insufficiency, these also risk to the development of a pressure ulcer, and many wounds, especially in the lower extremity, have a multifactorial etiology. Braden assessment tools fail to hold many of the intrinsic risk factors for pressure ulcers, and may be inaccurate. Purpose: The purpose of this paper was to resolve the controversy between avoidable and unavoidable pressure ulcer in some patient’s condition, especially among terminally ill cancer patients. Methodology: A literature review was conducted by searching in PubMed, Science Direct, EBSCO, and Google Scholar by using keys word: Unavoidable pressure ulcer, Incidence of pressure ulcer, Pressure ulcers Factors. Conclusion: Pressure ulcer is sometimes unavoidable for patients at risk, even in the best circumstances. However, the acknowledgment that some pressure ulcers are inevitable should never deter the implementation of risk assessment, skin examination, preventive interventions, or the search for new technologies to prevent this end result. Recommendations: 1. Further study is needed to determine the degree to which resources and intrinsic factors contribute to pressure ulcer development. 2. Continued study is needed to support the creation of an expanded list of risk factors that are more predictive of pressure ulcer development. 3. Clinical practice guidelines should be formulated to address patient management when death is expected a